Síntese e caracterização da polianilina dopada com ácido oléico e preparação de seus híbridos com ferritas de cobalto para aplicação em fotodegradação - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
Polyaniline (PAni ) is one of the most widely studied conducting polymers in the last two decades. The physico - chemical properties that polyaniline offers associated with good environmental stability has attracted the attention of scientists in the preparation of hybrids. The use of polyaniline associated with inorganic particles such as cobalt ferrite, it has been proposed due to possible applications of these materials, as the photocatalytic action. The objective of this study is synthesize polyaniline doped with oleic acid (OA) and prepare hybrids with cobalt ferrite for application in photodegradation of methylene blue and characterize them by X-ray powder diffraction (DRX), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), transmission electronic microscopy (MET), electrical conductivity measurements by four-point method, Mossbauer spectroscopy and magnetization curves. Two synthesis routes were performed to obtain the PAni (OA). The first route in order to obtain PAni (OA) was performed by the chemical polymerization of aniline, highlighting influence of four factors: the volume effect of synthesis, the addition of solvent (ethanol), the washing process of filtrate and the mole ratio oleic acid/aniline. The second route was performed by reprotonation of emeraldine base. The following parameters were studied in the process of obtaining cobalt ferrite by coprecipitation method: the influence of temperature on the direct synthesis process, the influence of temperature on the breakdown process and the type of stirring process. The PAni (OA)/cobalt ferrite hybrid was obtained by in situ polymerization of aniline/oleic acid in the presence of cobalt ferrite ranging the mass ratio of aniline and cobalt ferrite 1:0.5, 1:1, 1:1.5, and 1:2. The results obtained in this work through the characterizations showed formation of PAni (AO), cobalt ferrite and hybrid PAni (AO)/cobalt ferrite. The results showed higher yields to 77 % and electrical conductivity on the order 10-3 S∙cm-1 for samples of PAni (OA) obtained by the oxidation of aniline. The characterizations performed on the samples of cobalt ferrite suggest the existence of phase with spinel-type CoFe2O4 structure with a mean diameter of crystallites 10.67 nm and electrical conductivity on the order of 10-5 S∙cm-1, corresponding to its character semiconductor. The samples of the PAni (OA)/cobalt ferrite hybrid showed electric conductivity on the order of 10-3 and 10-4 S.cm-1 and saturation magnetization values between 4.02 and 17.2 emu/g. The photocatalytic action of PAni (OA), cobalt ferrite and hybrid PAni (OA)/cobalt ferrite was analyzed using aqueous solution of methylene blue, through irradiation evaluating the time exposure. The irradiated samples were analyzed by UV-Vis spectrophotometry and graphs were obtained and monitored the concentration of methylene blue as a function of time of exposure to radiation. The PAni (OA) and hybrid PAni (OA)/cobalt ferrite samples showed satisfactory results of photocatalytic action using ultraviolet and visible radiation. The cobalt ferrite samples showed photocatalytic capacity using visible radiation. In all cases, the intensity reduction of the absorbance over time of irradiation was adjusted satisfactorily to the kinetic model of Langmuir-Hinshelwood pseudo first order.
Keywords: Polianilina; Ferrita de cobalto; Híbridos; Fotodegradação; Polyaniline; Cobalt ferrite; Hybrids; photodegradation; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA